Webster's New world college dictionary (Boston : Houghton Mifflin Harcourt, 2014)
Webster's new world college dictionary, fifth edition, presents a clear and accessible defining style, abundant synonym notes, full-page tables and charts, hundreds of drawings that complement the definitions and authoritative guidance on usage and style points plus it has added more than 4,700 entries and senses have been added, including terms from the areas of arts and sports, science and medicine, computers and the Internet, food, business, politics, and law. Tens of thousands of revisions have been made to existing senses, to bring them up-to-date and to reflect current usage.
Keywords: English language -- Dictionaries